2014
DOI: 10.1186/2197-4284-1-9
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of site-specific and basin-scale denudation rate estimation by in situ cosmogenic nuclides: an example from the Abukuma Mountains, Japan

Abstract: Accurate determination of denudation rates is important in understanding Earth surface system dynamics. In situ produced cosmogenic nuclides, such as 10 Be and 26 Al, provide a valuable insight but are not entirely free from complications. In this study, denudation rates are determined for the Abukuma Mountains, Japan, using both site-specific and basin-scale methods. Considered with density measured in the field, distinct and systematic differences between the two methods are identified. Site-specific rates c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Some studies report spatial variations in soil carbon along ridge top to hillslope (Harden et al, 2002;Yoo et al, 2006). Considering the difference in erosion rates within a watershed (Heimsath et al, 1999(Heimsath et al, , 2001Nakamura et al, 2014a), monsoon-induced fluctuations in the spatial pattern of soil erosion could change the oldcarbon offset. Consequently, further research into understanding the mechanism of the old-carbon offset is not only important for sediment geochronology, but also strongly related to vegetation and soil carbon dynamics.…”
Section: Mechanisms Of Organic Matter Deposition In Lake Raramentioning
confidence: 96%
“…Some studies report spatial variations in soil carbon along ridge top to hillslope (Harden et al, 2002;Yoo et al, 2006). Considering the difference in erosion rates within a watershed (Heimsath et al, 1999(Heimsath et al, , 2001Nakamura et al, 2014a), monsoon-induced fluctuations in the spatial pattern of soil erosion could change the oldcarbon offset. Consequently, further research into understanding the mechanism of the old-carbon offset is not only important for sediment geochronology, but also strongly related to vegetation and soil carbon dynamics.…”
Section: Mechanisms Of Organic Matter Deposition In Lake Raramentioning
confidence: 96%
“…Contributions of slow and fast muons to the total 10 Be production at the surface were assumed to be 1.2% and 0.65%, respectively (Braucher et al, 2003). We assumed a bulk density of 1.63 g/cm 3 for the shallow subsurface materials on hillslopes (Nakamura et al, 2014). Although it sometimes snows in Iwaki, we did not consider the effect of snow shielding on 10 Be production because the snow cover was mostly less than several centimeters deep during 1960-2008 (Japan Meteorological Agency, 2021).…”
Section: Basin-averaged Erosion Rate Determined From Cosmogenic 10 Be...mentioning
confidence: 99%
“…To verify these estimates, we calculated erodibility coefficients for similar granitic rocks in the Abukuma massif (Kubo & Yamamoto, 1990) north of the study area using the same DEM and procedure we used in Iwaki (Figure S4; Tables S3, S4). We relied on 10 Be concentrations of fluvial sand reported by Regalla et al (2013), Nakamura et al (2014), and Matsushi et al (2014) to recalculate basin-averaged erosion rates using the same method used in Iwaki. The resulting erodibility coefficients were similar to those obtained in Iwaki: 1.58×10 −5 (𝑛 = 2/3), 4.52×10 −6 (𝑛 = 1), and 3.90×10 −7 (𝑛 = 5/3) m 0.1 /yr.…”
Section: Substrate Erodibility Calculated From Basin-averaged Erosion...mentioning
confidence: 99%
“…Fujiwara et al (2001) reported average basin-scale denudation rates of ~ 0.132 mm/ year in the Abukuma Mountains based on the relationship between sediment delivery rates to reservoirs and the dispersion of elevation. Nakamura et al (2014) estimated denudation rates in the Abukuma Mountains of 0.114-0.180 mm/year based on the concentration of cosmogenic nuclides in fluvial sediments. Although we cannot discuss the slip rate of the Mochiyama fault directly due to lack of cumulative offsets on fluvial terrace or alluvium, these previous studies suggest that the slip rate of the Mochiyama fault is no greater than ~ 0.1 mm/ year.…”
Section: Detection and Assessment Of Slow Slip-rate Faultsmentioning
confidence: 99%